BERMAIN TWISTER MODIFIKASI TERHADAP HASIL BELAJAR MENGENAL BENTUK GEOMETRI SISWA AUTIS PADA SEKOLAH LUAR BIASA - Adi Hutama, Briyan (Jurnal Pendidikan Khusus, 2017)
Abstract:  Geometry is a branch of mathematics that are important to be studied by all students. Because by studying geoemetri to stimulate students to think critically and logically. Children with autism have a bottleneck in the cognitive because the barriers found in the hippocampus area that caused the student with autism is difficult to accept and store the new information so the effect on the autistic student learning outcomes. It is evident from the observations made in SLB Harapan Mulya Driyorejo, 6 students with autism get a low learning outcomes in recognizing geometric shapes. Accordingly, because it required a learning method that suits the character and abilities of children with autism, one through playing twister modification. This study aims to examine effect of play twister modifications to the learning outcomes of students with autism recognize geometric shapes in SLB Harapan Mulya Driyorejo Gresik. The research approach used is the quantitative approach. This type of research is pre-experimental research. The study design used is the one group pretest posttest. To use a non-parametric data analysis. The results showed that there are influences that occur in students with autism in recognizing geometric shapes through playing twister modification. Evidenced by the difference between pretest and posttest value is 60.41. Based on these values and then analyzed the data using Wilcoxon test with a standard error of 5% so Ztabel = 1.96. Z value is obtained within ZH = 2.21. It can be concluded that playing twister modification positive effect on the learning outcomes of students with autism recognize geometric shapes with ZH = 2.21 a value greater than the value Ztabel 5% = 1.96.   Keywords: twister modification, geometric shapes